MHD Flow of Carreau Liquid with Partial Slip and Newtonian Heating - Eswaramoorthi, S.; Loganathan, K.; Sivasankaran, S.; Bhuvaneswari, M.; Rajan, S. (International Journal of Engineering and Technology, 2018)
This work deliberates the MHD flow of Carreau liquid past a stretching plate with thermal radiation, viscous dissipation and Joule heating. Additionally, partial velocity slip and Newtonian heating effects are included in our study. The similarity transformations are used to convert the governing dimensional partial differential equations into dimensionless ordinary differential equations. Homotopy analysis method (HAM) is employed to find the convergent series solutions of the governed non-linear ordinary differential equations. It is found that the magnetic field parameter slowdown the liquid motion and rises the liquid temperature. In addition, heat generation parameter enhances the thermal boundary layer thickness and chemical reaction parameter suppresses the solutal boundary layer thickness.Â Â